Interplay Between m6A RNA Methylation and Regulation of Metabolism in Cancer - Mobet, Youchaou; Liu, Xiaoyi; Liu, Tao; Yu, Jianhua; Yi, Ping (Frontiers in Cell and Developmental Biology, 2022)
Methylation of adenosine in RNA to N6-methyladenosine (m6A) is widespread in eukaryotic cells. This dynamic process is regulated by methylases (writers), demethylases (erasers), and proteins that recognize methylation (readers). It is now evident that m6A is involved in the proliferation and metastasis of cancer cells, for example, altering cancer cell metabolism. Thus, determining how m6A dysregulates metabolic pathways could provide potential targets for cancer therapy or early diagnosis. In this review, we focus on the link between the m6A modification and the reprogramming of metabolism in cancer. We hypothesize that m6A modification could dysregulate the expression of glucose, lipid, amino acid metabolism and other metabolites or building blocks of cells by adaptation to hypoxic tumor microenvironment, an increase in glycolysis, mitochondrial dysfunction, and abnormal expression of metabolic enzymes, metabolic receptors, transcription factors as well as oncogenic signaling pathways in both hematological malignancies and solid tumors. These abnormalities of the metabolism caused by m6A’s modification may affect metabolic reprogramming of cancer cells and then increases cancer cell proliferation as well as tumor initiation and metastasis. We conclude that focusing on m6A could provide new directions in the search for novel therapeutic and diagnostic targets for early detection and treatment of many cancers.